Mitochondria: a breakthrough in combating rheumatoid arthritis - Li, Shuang; Huo, Chenlu; Liu, Anting; Zhu, Yan (Frontiers in Medicine, 2024)
As a chronic autoimmune disease with complex aetiology, rheumatoid arthritis (RA) has been demonstrated to be associated with mitochondrial dysfunction since mitochondrial dysfunction can affect the survival, activation, and differentiation of immune and non-immune cells involved in the pathogenesis of RA. Nevertheless, the mechanism behind mitochondrial dysfunction in RA remains uncertain. Accordingly, this review addresses the possible role and mechanisms of mitochondrial dysfunction in RA and discusses the potential and challenges of mitochondria as a potential therapeutic strategy for RA, thereby providing a breakthrough point in the prevention and treatment of RA.